Pendidikan Agama Islam dalam Lanskap Post Tradisionalisme Islam - Susanto, Edi (Program Pascasarjana UIN Sunan Ampel Surabaya, 2012)
This paper is interested in exploring the most recent current of thought belonging to the younger generation of Indonesian intelligentsia. This current of thought is known by many as post-traditionalism. While discussing some of its most notable traits, this paper tries to show that the school of thought âwhile being intellectual and discursive- is also concerned with the state of education in the country. The paper argues first and foremost that the advent of this school was due to the poor quality of religious discourse in the country. By means of critical approach and âleftistâ epistemology, this group tries to subvert the existing discourses, which it considers irrelevant. Since these irrelevant doctrines were encapsulated in the educational institutions, the practical and strategic way to dismantle these doctrines is by deconstructing their educational system on the one hand, and by reconstructing the new one; the one that reflects the universal and humanitarian values of Islam such tolerance and understanding.